Percutaneous Coronary Intervention Outcomes by 5 Major Race and Ethnic Subgroups - Arjun B. Kapoor, MD; Serdar Farhan, MD; Manish Vinayak, MD; Samantha Sartori, PhD; Yihan Feng, MS; Yash Prakash, MD; Roxana Mehran, MD; Annapoorna Kini, MD; Deepak L. Bhatt, MD, MPH, MBA; Samin K. Sharma, MD (JACC: Advances)
Background: Racial and ethnic disparities in cardiovascular disease outcomes, including percutaneous coronary intervention (PCI), are well-documented. However, studies do not stratify certain subgroups, such as separating South Asian and East Asian patients, who exhibit varying burdens of cardiovascular disease and PCI outcomes. Additionally, socioeconomic status (SES) further complicates outcomes, with low SES serving as an independent predictor of adverse outcomes post-PCI. Objectives: This study aimed to analyze PCI outcomes across 5 racial and ethnic groups—White, Black, Hispanic, South Asian, and East Asian populations—while accounting for comorbidities and SES to better understand how race and ethnicity influence cardiovascular outcomes. Methods: We conducted a retrospective cohort study of patients undergoing PCI from 2012 to 2022. Patients were stratified by race/ethnicity and matched to median household income based on U.S. Census Zone Improvement Plan code data. The primary endpoint was 1-year major adverse cardiovascular events (MACE). Multivariable Cox regression models were used to assess outcomes, adjusting for comorbidities and SES. Results: A total of 21,236 patients were included: 47.8% White, 11.3% Black, 18.0% Hispanic, 20.7% South Asian, and 2.2% East Asian. South Asian patients had significantly lower MACE (adjusted HR: 0.62; P < 0.001) compared with White patients. Black patients, in contrast, had a higher risk of MACE (adjusted HR: 1.27; P = 0.032). Conclusions: Significant racial and ethnic disparities exist in 1-year PCI outcomes, with South Asian patients exhibiting favorable outcomes compared with White patients, and Black patients experiencing worse outcomes. Baseline comorbidities and estimated SES do not fully explain these disparities, suggesting that targeted strategies are needed to address the multifactorial influences on PCI outcomes across racial and ethnic groups.